Factors contributing to financial literacy among MSMEs in Klang Valley - Hamdan, Hamdino; Abdul Razak, Dzuljastri; Huridi, Mohd Hanafia; Uddin, Md Nazim (Abdullah Kuzu, 2021)
Micro small and medium-sized enterprises (MSMEs) contribute significantly to the economic and social development of many countries. In particular, the sector provides new job opportunities, stimulates competition and thus boost productivity. Accordingly, the sustainability of MSMEs is of paramount importance. However, according to Fatoki (2012) 60% of MSMEs fail within the first five years of their operations. One of the reasons of this failure is poor financial management which is mainly because of poor financial literacy. Financial literacy is also an issue highlighted in the human resource ability in accessing fund from financial institution. Therefore, the purpose of this paper is to assess the level of financial literacy among Amanah Ikhtiar Malaysia (AIM) MSMEs operator in Klang Valley from three different districts of Selangor. A structured questionnaire was used to collect data from 312 AIM MSMEs operator. Descriptive and inferential analysis are used to examine the extent of awareness regarding financial literacy among AIM MSMEs operator. The findings indicated that ANOVA result significantly influences financial literacy. The study results indicated that knowledge, socialisation agents, attitude and skills are significant predictors of financial literacy among AIM MSMEs operator in Klang Valley, Malaysia. Thus, policymakers should consider MSMEs factors and financial literacy traits, which determine their behaviours and actions in micro-entrepreneurship while implementing financial literacy interventions to promote financial inclusion of MSMEs, especially in Klang Valley, Malaysia.